La problemática tributaria de los contratos de asociación en participación - Salazar Mesías, Octavio (2018)
In this article, the author analyzes the tax regime linked to the partnership agreement (joint venture) agreement, within the framework of a recent court resolution by the administrative authority on tax matters. In this regard, the author presents an interesting summary of the normative changes that took place around the partnership agreement, and presents us with an interesting position concerning the effects that the Tax Court Resolution would have on taxpayers. Finally, emphasizing the scenario of uncertainty surrounding the figure described, the author urges the creation of appropriate standards that provide legal security to the actors in the market.